Wittgenstein's beetle: And other classic thought experiments - Cohen, Martin (Malden Blackwell, 2005)
"Wittgenstein's Beetle and Other Classic Thought Experiments" invites readers to participate actively in discovering the surprisingly powerful and fruitful tradition of 'thought experiments'. This work: gives a lively presentation of an 'A to Z' of 26 fascinating and influential thought experiments from philosophy and science; presents vivid and often humorous discussion of the experiments, including strengths and weaknesses, historical context, and contemporary uses; provides a 'how to' section for engaging in thought experiments; and, includes illustrations, mini-biographies, and suggestions for further reading.